Genome-wide mapping of genetic determinants influencing DNA methylation and gene expression in human hippocampus. Issue 1 (December 2017) - Schulz, Herbert; Ruppert, Ann-Kathrin; Herms, Stefan; Wolf, Christiane; Mirza-Schreiber, Nazanin; Stegle, Oliver; Czamara, Darina; Forstner, Andreas; Sivalingam, Sugirthan; Schoch, Susanne; Moebus, Susanne; Pütz, Benno; et al.
Abstract Emerging evidence emphasizes the strong impact of regulatory genomic elements in neurodevelopmental processes and the complex pathways of brain disorders. The present genome-wide quantitative trait loci analyses explore thecis -regulatory effects of single-nucleotide polymorphisms (SNPs) on DNA methylation (meQTL) and gene expression (eQTL) in 110 human hippocampal biopsies. We identifycis -meQTLs at 14, 118 CpG methylation sites andcis -eQTLs for 302 3′-mRNA transcripts of 288 genes. Hippocampalcis -meQTL-CpGs are enriched in flanking regions of active promoters, CpG island shores, binding sites of the transcription factor CTCF and brain eQTLs.Cis -acting SNPs of hippocampal meQTLs and eQTLs significantly overlap schizophrenia-associated SNPs. Correlations of CpG methylation and RNA expression are found for 34 genes. Our comprehensive maps ofcis -acting hippocampal meQTLs and eQTLs provide a link between disease-associated SNPs and the regulatory genome that will improve the functional interpretation of non-coding genetic variants in the molecular genetic dissection of brain disorders. Most SNPs are located in non-coding genomic regions and their function remains elusive. Here, the authors perform a genome-wide scan of expression and DNA methylation quantitative trait loci in human hippocampal tissue to provide a resource for the functional interpretation of SNPs in brain disorders.